2009
DOI: 10.1007/s00253-009-2359-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrite inhibition on anaerobic ammonium oxidation

Abstract: In order to assess the stability of nitrogen removal systems utilizing anaerobic ammonium oxidation (anammox), it is necessary to study the toxic effects of nitrite on these biochemical reactions. In this study, the effects of nitrite on anammox bacteria entrapped in gel carriers were investigated using batch and continuous feeding tests. The results showed that the nitrite concentration in a reactor must be less than 274-mg N/L in order to prevent a decrease in the anammox activity, which occurred when the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(32 citation statements)
references
References 11 publications
2
26
1
3
Order By: Relevance
“…Some previous researchers reported that the anammox activity decrease by a half when influent NO 2 --N concentration was above 350 mg-N l -1 (Dapena et al 2007) or 37% under influent NO 2 --N concentration of 430 mg-N l -1 (Kimura et al 2010). The results achieved from our study were different from their results.…”
Section: Effect Of Influent Nitrite Concentrationcontrasting
confidence: 85%
“…Some previous researchers reported that the anammox activity decrease by a half when influent NO 2 --N concentration was above 350 mg-N l -1 (Dapena et al 2007) or 37% under influent NO 2 --N concentration of 430 mg-N l -1 (Kimura et al 2010). The results achieved from our study were different from their results.…”
Section: Effect Of Influent Nitrite Concentrationcontrasting
confidence: 85%
“…However, both substrates act as potential inhibitors to the growth and metabolism of Anammox bacteria when their concentrations exceed the threshold inhibitory values [5,[12][13][14][15][16][17][18]. So, the substrate inhibition must be avoided during the operation of Anammox bioreactors.…”
Section: Introductionmentioning
confidence: 99%
“…confirmed that nitrite concentration less than 280 mg L −1 was suitable for anammox reaction. Kimura et al . concluded that anammox activity loss of 35% was observed only at concentrations higher than 274 mg L −1 in PEG immobilized gels during batch tests.…”
Section: Recent Developments In Anammox Immobilizationmentioning
confidence: 99%
“…Isaka et al 122 confirmed that nitrite concentration less than 280 mg L −1 was suitable for anammox reaction. Kimura et al 88 concluded that anammox activity loss of 35% was observed only at concentrations higher than 274 mg L −1 in PEG immobilized gels during batch tests. The same was again confirmed in PVA cryogels by Magrí et al 44 During continuous operation, nitrite concentration up to 400 mg L −1 does not inhibit anammox bacteria and 90% anammox activity was decreased at a concentration of 700 mg L −1 .…”
Section: Advantages Of Immobilized Anammox Organisms Compared With Otmentioning
confidence: 99%
See 1 more Smart Citation